Interleukin-10-1082A/G and −592C/A Polymorphisms with risk of Parkinson's disease: a meta-analysis. (2nd November 2014) - Jin, Jun; Wu, Peihua; Li, Wuying; Shi, Jian; Chen, Jian; Li, Rong; Tan, Sheng
<x xml:space="preserve">Abstract</x> Several studies have been conducted in recent years to evaluate the risk of Parkinson's disease (PD) and polymorphisms of interleukin-10 (IL-10). However, the results were conflicting. Therefore, we performed this meta-analysis of published case–control studies to assess this association. Systematic searches of electronic databases PubMed Web of Science, BIOSIS Previews, Science Direct, Chinese Biomedical Database, WANFANG Database, and Chinese National Knowledge Infrastructure with hand searching of the references of identified articles were conducted. Data were extracted using a standardized form and pooled odd ratios with 95% confidence intervals were calculated to evaluate the strength of the association. A total of seven case–control studies involving 1912 PD cases and 1740 controls were included, concerning two polymorphisms (−1082A/G and −592C/A) of IL-10 gene. No significant associations were found in the overall analysis for both −1082A/G and −592C/A polymorphisms with PD risk. Similar lacking associations were observed in subgroup analysis based on ethnicity and age of onset. In conclusion, there is no enough evidence for association between IL-10 polymorphisms (−1082A/G and −592C/A) and risk of PD at present. Well-designed studies with larger sample size and multi-ethnicity studies are warranted in the future.